2020
DOI: 10.5037/jomr.2020.11302
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary Sinus Floor Augmentation with Autogenous Bone Graft Alone Compared with Alternate Grafting Materials: a Systematic Review and Meta-Analysis Focusing on Histomorphometric Outcome

Abstract: Objectives The objective of present systematic review was to test the hypothesis of no difference in histomorphometric outcome after maxillary sinus floor augmentation with autogenous bone graft alone compared with alternate grafting materials applying the lateral window technique. Material and Methods MEDLINE (PubMed), Embase and Cochrane library search in combination with hand-search of relevant journals were conducted. Human studies published in English until the 25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 63 publications
(336 reference statements)
1
12
0
Order By: Relevance
“…In addition, our maxillary sinus augmentation surgery was performed in closed space, therefore bone grafts are less likely to leak from the void space. These findings are supported by previous studies that used histomorphometry as a major method to investigate the difference between grafts and found that DBB resorption was slower than other graft materials 11,28 …”
Section: Resultssupporting
confidence: 84%
“…In addition, our maxillary sinus augmentation surgery was performed in closed space, therefore bone grafts are less likely to leak from the void space. These findings are supported by previous studies that used histomorphometry as a major method to investigate the difference between grafts and found that DBB resorption was slower than other graft materials 11,28 …”
Section: Resultssupporting
confidence: 84%
“…Nevertheless, patients with impaired OHRQoL generally Table 4 Percentage distribution of responses to each question of OHIP-14 questionnaire 0 = never; 1 = hardly ever or nearly never; 2 = occasionally; 3 = fairly often or many times; 4 = very often BBGM biphasic bone graft material, DPBM deproteinized porcine bone mineral, SD standard deviation significantly associated with impaired patient´s perception of recovery. MSFA with autogenous bone graft used alone or in combination with different ratios of bone substitutes generates more newly formed bone, higher bone-toimplant contact, and earlier bone formation compared with the use of a bone substitute alone [13,[29][30][31]. However, harvesting of extraoral and intraoral autogenous bone graft negatively influences postsurgical OHRQoL due to increased pain, impaired eating and speaking ability, sleep impairment, limitation in daily routine, and sick leave [12,[32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…MSFA with autogenous bone graft used alone or in combination with different ratios of bone substitutes generates more newly formed bone, higher bone-to-implant contact, and earlier bone formation compared with the use of a bone substitute alone [ 13 , 29 31 ]. However, harvesting of extraoral and intraoral autogenous bone graft negatively influences postsurgical OHRQoL due to increased pain, impaired eating and speaking ability, sleep impairment, limitation in daily routine, and sick leave [ 12 , 32 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Autogenous bone (AB) harvested from intraoral or extraoral sources is generally considered as the preferred graft due to its osteoinductive, osteoconductive, and osteogenic properties. It has been concluded in recently published systematic reviews focusing on histomorphometric assessment after MSFA that AB enables the highest amount of bone formation compared with other biomaterials (Corbella et al, 2016; Danesh‐Sani et al, 2017; Starch‐Jensen et al, 2020). However, AB is associated with unpredictable resorption of the graft, which may compromise staged implant placement or necessitates additional bone augmentation (Pesce et al, 2021; Shanbhag et al, 2014).…”
Section: Introductionmentioning
confidence: 99%